Augmented Pokemon Go in Times of Covid-19: Does it Have any Effect on Promoting Teenagers’ Physical Activity? - Hasanuddin Jumareng; Edi Setiawan; Zsolt Németh (Physical Education Theory and Methodology, 2022)
Study purpose. One of the main problems during the COVID-19 pandemic that needs to be considered is the decline in physical activity carried out by teenagers. The overall objective of this mixed method is to investigate the effects of the Pokemon Go intervention program to promote physical activity in teenagers during the COVID-19 crisis.